Brain-on-a-chip: A history of development and future perspective - Bang, Seokyoung; Jeong, Sohyeon; Choi, Nakwon; Kim, Hong Nam (Biomicrofluidics, 2019)
Since the advent of organ-on-a-chip, many researchers have tried to mimic the physiology of human tissue on an engineered platform. In the case of brain tissue, structural connections and cell–cell interactions are important factors for brain function. The recent development of brain-on-a-chip is an effort to mimic those structural and functional aspects of brain tissue within a miniaturized engineered platform. From this perspective, we provide an overview of trace of brain-on-a-chip development, especially in terms of complexity and high-content/high-throughput screening capabilities, and future perspectives on more in vivo-like brain-on-a-chip development.